2022
DOI: 10.3390/vaccines10081324
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Humoral and Cellular Immunogenicity of the BNT162b2 SARS-CoV-2 Vaccine in Liver-Transplanted Adolescents Compared to Healthy Adolescents

Abstract: Since BNT162b2 was approved to prevent COVID-19 in children, we aim to compare the safety and immunogenicity of the BNT162b2 vaccine in liver-transplanted (LT) and healthy adolescents. LT and healthy adolescents received two doses of 30 µg of BNT162b2. All were evaluated for total COVID-19 antibodies directed against the receptor-binding domain (RBD) and interferon-γ using the ELISpot at all time points; anti-nucleocapsid immunoglobulin was evaluated at week 8 and the surrogate virus-neutralizing antibody (sVN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…We reported higher antibody response to BNT162b2 vaccine in young liver-transplanted recipients compared to adult cohorts, as observed by Sintusek et al (8). Similar to the observation by these authors, all participants in our study showed antibody response, compared to 73.3% reported by Qin et al (7) in solid-organ transplanted children.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We reported higher antibody response to BNT162b2 vaccine in young liver-transplanted recipients compared to adult cohorts, as observed by Sintusek et al (8). Similar to the observation by these authors, all participants in our study showed antibody response, compared to 73.3% reported by Qin et al (7) in solid-organ transplanted children.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings suggest that adolescent with liver transplantation are able to mount robust immune responses to SARS-CoV-2 vaccination. As expected for younger cohorts, our patients showed higher percentages of immune responses when compared to older liver-transplanted recipients ( 6 8 ). The more information we have about the immune response against SARS-CoV-2 in immunosuppressed transplanted patients, the better we can establish the risk of developing disease following infection ( 19 ).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations